Building trust in e-commerce: a proposed Shari’ah compliant model - Muhammad, Muhd. Rosydi; Muhammad, Marjan (Array Development Canada (JIBC), 2013)
Studies show that trust has a significant impact on users’ motivation, acceptance and willingness for e-commerce dealings. Existing literature investigates the role of trust in e-commerce environment within the conventional space but scarcely looks into the issue from the Islamic perspective. Considering that Muslim users constitute a relatively significant percentage of the whole online commerce community, it is pertinent to understand the concept of trust in the light of Shari’ah. Inability to satisfy religio-centric attitude of the Muslim internet users may bring negative consequences for the overall success of e-commerce environment. Therefore, the main objective of this study is to explore how to build online trust among Muslim users through an analysis of the essential requirements of e-commerce from the perspective of Islamic law of contract. The literature review covers empirical studies on the concept of trust, model of trust and Islamic law of contract. For the review, library research is employed by the means of investigating classical and contemporary literature to search for information on essential requirements underpinning e-commerce contracts. The study sheds light on some conditions related to offer and acceptance (form), buyer and seller (parties), and object and price (subject matter) of sale contracts concluded via online environment. An appraisal of these issues will justify the validity of e-commerce in Islamic law, thus enhancing the level of online trust among Muslim users. Drawing upon these discussions, a Shari’ah compliant model for online trust is proposed highlighting essential requirements of Islamic law of contract as variables for online trust.